Clinical significance of FLG gene mutations in children with atopic dermatitis - E. E. Varlamov (Rossijskij Vestnik Perinatologii i Pediatrii, 2016)
Skin barrier dysfunction due to deficiency of the skin protein filaggrin is one of the factors involved in the pathogenesis of atopic dermatitis. Objective: to determine the clinical significance of 2282 del CAGT, R501X, R2447X, and S3247X mutations in the FLG gene in children with atopic dermatitis. The investigation included 58 children with atopic dermatitis. A molecular genetic analysis of the four mutations in the FLG gene was done in all the children. In the patients with FLG gene mutations, there was a tendency towards a higher frequency of sensitization to house dust allergens, significantly more often sensitization to cat epidermal allergen, and significantly higher levels of specific IgE to the cat epidermis. Conclusion. Mutations in the FLG gene encoding the protein filaggrin raise the risk for sensitization to domestic and epidermal allergens and, in case of already existing sensitization to the cat epidermis, the patients are found with a high degree of probability to have the high concentration of specific IgE to this allergen. The above fact justifies the need to place special emphasis on measures to eliminate house dust allergens, and cat epidermis allergen in particular, and to personalize approaches to therapy and prevention of atopic dermatitis in children.